The Effect Of Transparency , Accountability And Leadership On The Effectiveness Of Village Fund Management - Kristiansen, Stein; Yusuf, Muhammad; Komiya, Kazutaka (Journal of Management, 2022)
Study This goal To examine the empirical impact of transparency, accountability, and leadership on the efficiency of village fund administration in the villages of Cinunuk and Cimekar district, Regency. Bandung. Study this is research Using quantitative methods and primary data, this information was gathered from respondents using a questionnaire that was given to 48 government employees' villages. people being studied This is the staff government for the Cileunyi Regency in Bandung's villages of Cinunuk and Cimekar. Data analysis employed the multiple linear regression test, the heteroscedasticity test, the multicollinearity test, and the normality test. According to research findings, accountability, transparency, and leadership all contribute to good village fund management.